KEEFEKTIFAN OFFICIAL WEBLOG SEBAGAI MEDIA PROMOSI DESA WISATA SALAK PONDOH PULESARI KECAMATAN TURI KABUPATEN SLEMAN - Fadhila, Arintya Putri; Wastutingsih, Sri Peni; Untari, Dyah Woro (Berkala Ilmiah AGRIDEVINA, 2017)
Nowadays, promotion not only as offline activity but also, keeping pace with thedevelopment of technology and communication, promotion can be done by    online.One of online promotion is using weblog as promotion media.   Weblog can be usedas promotion media because it has possibility to 2-way communication, between user andvisitors. This research concerns about weblog of Pulesari Tourism Villagedesawisatapulesari. wordpress.com, with purposes: 1) determine the effectivity level ofPulesari Tourism Village’s weblog as promotion media. 2) determine the factors relatedto the effectivity Pulesari Tourism Village’s weblog as promotion media. Purposivesampling was used in this research with 50 selected visitors of Pulesari Tourism Villageas sample. The analysis methods used in this research were proportion test and chisquare. The effectivity, include three effects i.e. cognitive effect, affective effect andpsycomotoric effect. Cognitive effect means knowledge growth, affective effect meansattitude and psycomotoric effect means behavior. The research results showed that theeffectivity level was categorized as high (>50%). Factors that related to the weblogeffectivity, were content, completeness, credibility, perception and response. Contenthas gamma score 0,514, completeness 0,685, credibility 0,633, perception 0,630 andresponse 0,583. All factors have  middle-strong positive relation to  the effectivity of Pulesari Tourism Village’s weblog as promotion media.